Perngaruh Leverage, Likuiditas, Dan Profitabilitas Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur - Revita Apriliani, Ardiansyah (Jurnal Paradigma Akuntansi, 2019)
This research has a purpose to obtain empirical evidence regarding the effect of liquidity, leverage, and profitability on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. This study selected data with purposive sampling technique and selected 106 samples that met the criteria. The research data was processed using SPSS (Statistical Product and Service Solution) Version 23rd. The results showed that liquidity with a proxy current ratio and leverage with a debt to equity ratio proxy simultaneously had a negative and not significant effect on dividend policy. Meanwhile, profitability with a return on equity proxy has a positive and significant effect on dividend policy. Simultaneously, liquidity, leverage, and profitability influence dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017